Multiple forest attributes underpin the supply of multiple ecosystem services - María R. Felipe-Lucia (Nature Portfolio, 2018)
Managing forests for the supply of multiple ecosystem services (ES) is key given potential trade-offs among services. Here, the authors analyse how forest stand attributes generate trade-offs among ES and the relative contribution of forest attributes and environmental factors to predict services.